Modeling consumer’s innovativeness and purchase intention relationship regarding 5G technology in China - Shah, Sayed Kifayat; Tang, Zhongjun; Gavurova, Beata; Oláh, Judit; Acevedo-Duque, Ángel (Frontiers in Environmental Science, 2022)
Consumer innovativeness is a significant personality attribute that refers to a person's proclivity to acquire and utilize new items more rapidly and frequently than others. Although previous research has revealed a relationship between consumer innovativeness and the intention to buy new technology products, little is known about the determinants such as visibility and guidance affordances, environmental awareness, and safety concerns that underpin this relationship. Using the diffusion of innovation (DOI) theory through the PLS-SEM approach, this study analyzed the data of 341 Chinese consumers to explore the prospects mentioned above. Empirical results show that visibility and guidance affordances encourage consumer innovativeness. The results further reveal that environmental awareness and product safety concerns mediate the consumer innovativeness and purchase intention relationship. This model will contribute to the literature by improving predictive ability over previous models. Therefore, managers and policy-makers who wish to make constructive changes in the intentions of technology consumers are encouraged to ruminate on the extrapolations of this article.